Unusual Benign Middle Ear Tumors: How Does the Presentation Differ from Otitis Media? - Krutika Sonvane; Navnit Makwana; Rahul Gupta; Hardik Patel; R G Aiyer (Bengal Journal of Otolaryngology and Head Neck Surgery)
Introduction: Middle ear tumors represents a rare group of neoplasm that vary widely according to their pathology, anatomical involvements and clinical features. They mimic middle ear inflammatory pathologies intricately and hence early definitive diagnosis is a challenge. As these tumors are histologically benign, they are only locally destructive causing vestibular/facial dysfunction.